Leptospirosis in Wild and Domestic Carnivores in Natural Areas in Andalusia, Spain - Millán, Javier; Candela, Mónica; López-Bao, José Vicente; Pereira, Marian; Jiménez Martínez, María de los Ángeles; León-Vizcaíno, Luis (Vector-Borne and Zoonotic Diseases, 2009)
Leptospirosis is a zoonosis that affects humans, domestic animals, and wildlife. Carnivores are at the top of the feeding chain, thus being exposed to pathogens through their preys. From June 2004 to April 2007, we analyzed for evidences of contact with 14 serovars of Leptospira interrogans Sensu Lato serum (analyzed by indirect Microscopic Agglutination Test) and urine or kidney samples (analyzed by microscopic observation, immunostaining and culture) collected from 201 wild and domestic carnivores, including 26 free-living Iberian lynx (Lynx pardinus), 33 red foxes (Vulpes vulpes), 33 Egyptian mongooses (Herpestes ichneumon), 25 common genets (Genetta genetta), two Eurasian badgers (Meles meles) and one Eurasian otter (Lutra lutra), and 53 free-roaming cats and 28 rural dogs in protected areas in Andalusia (southern Spain). Twenty-three percent of the animals presented evidences of contact, being the prevalence similar among wild (23.5%) and domestic species (22.2%). Contact with Lesptospira was detected in all the species but the otter. Prevalence was: lynx (11% by bacteriological detection, 32% by serology), fox (0%, 47%), mongoose (5%, 20%), genet (0%, 12%), badger (0%, 50%), cat (20%, 14%), dog (only serology: 36%). Serovar Icterohemorragiae accounted for 2/3 of the cases. Serovar Canicola was detected in half of the positive dogs and one lynx. Other serovars detected were Ballum, Sejroë, and Australis. No macroscopic lesions were observed in necropsied animals that showed evidence of contact with the agent, although histopathologic lesions (chiefly chronic interstitial nephritis) were observed in 7 out of the 11 microscopically analyzed individuals. Thus, L. interrogans may cause previously unrecorded disease in wild carnivores in Spain. Wild and free-roaming carnivores may not act as reservoir of L. interrogans but as a dead-end hosts, though the dog may act as reservoir of serovar Canicola. Carnivores are apparently good sentinels for the epidemiological monitorization of leptospirosis Junta de ...